A Highly Automated Mobile Laboratory for On-site Molecular Diagnostics in the COVID-19 Pandemic. (31st March 2021) - Xing, Wanli; Wang, Jiadao; Zhao, Chao; Wang, Han; Bai, Liang; Pan, Liangbin; Li, Hang; Wang, Huili; Zhang, Zhi; Lu, Ying; Chen, Xiang; Shan, Sisi; et al.
Abstract: Background: Infectious disease outbreaks such as the COVID-19 (coronavirus disease 2019) pandemic call for rapid response and complete screening of the suspected community population to identify potential carriers of pathogens. Central laboratories rely on time-consuming sample collection methods that are rarely available in resource-limited settings. Methods: We present a highly automated and fully integrated mobile laboratory for fast deployment in response to infectious disease outbreaks. The mobile laboratory was equipped with a 6-axis robot arm for automated oropharyngeal swab specimen collection; virus in the collected specimen was inactivated rapidly using an infrared heating module. Nucleic acid extraction and nested isothermal amplification were performed by a "sample in, answer out" laboratory-on-a-chip system, and the result was automatically reported by the onboard information platform. Each module was evaluated using pseudovirus or clinical samples. Results: The mobile laboratory was stand-alone and self-sustaining and capable of on-site specimen collection, inactivation, analysis, and reporting. The automated sampling robot arm achieved sampling efficiency comparable to manual collection. The collected samples were inactivated in as short as 12 min with efficiency comparable to a water bath without damage to nucleic acid integrity. The limit of detection of the integrated microfluidic nucleic acid analyzer reached 150 copies/mL within 45 min. Clinical evaluation of the onboard microfluidic nucleic acid analyzer demonstrated good consistency with reverse transcription quantitative PCR with a κ coefficient of 0.979. Conclusions: The mobile laboratory provides a promising solution for fast deployment of medical diagnostic resources at critical junctions of infectious disease outbreaks and facilitates local containment of SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) transmission.